GESTÃO SOCIAL E CIDADANIA: UM PROJETO DE EXTENSÃO INTEGRADO A UMA REDE DE PESQUISA - Allebrandt, Sérgio L.; Cavalheiro, Marcos R. M.; Moraes, Naiara B. d.; Pereira, Ismael L. (Salão do Conhecimento, 2013)
Resumo